Control Model of SH-Synthesis for Two-Component Systems - Demyanuk D. G. Dmitry Georgievich; Dolmatov O. Yu. Oleg Yurevich; Isachenko D. S. Dmitry Sergeevich; Kuznetsov M. S. Mikhail Sergeyevich; Semenov A. O. Andrey Olegovich; Chursin S. S. Stanislav Sergeevich (2015, 2015)
Title screen